2020
DOI: 10.32604/chd.2020.011709
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Healthcare Utilization, Medical Cost, and Societal Cost in Adult Congenital Heart Disease

Abstract: Objective: Cost-of-illness studies in Adult Congenital Heart Disease (ACHD) have mainly been limited to hospitalizations. This is the first paper to provide a comprehensive overview from a societal perspective including inpatient and outpatient medical costs, and absenteeism-and unemployment-related societal costs. Methods: A retrospective longitudinal (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) database analysis was performed in Belgium combining administrative and clinical databases (n = 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…The outcome of CHD after the follow-up period revealed that almost 40% of patients with depression suffered from deteriorated health and that 60% had improved based on their cardiac parameters by echo and enzyme measurements. This finding is slightly lower than that of Willems R. et al, who reported that following their initial CHD-related admittance, 79% of people with CHD continued to go labour market with improved health [32]. The difference may be in the follow-up period; the follow-up was 3 months in our study and one year in the comparative study.…”
Section: Discussioncontrasting
confidence: 83%
“…The outcome of CHD after the follow-up period revealed that almost 40% of patients with depression suffered from deteriorated health and that 60% had improved based on their cardiac parameters by echo and enzyme measurements. This finding is slightly lower than that of Willems R. et al, who reported that following their initial CHD-related admittance, 79% of people with CHD continued to go labour market with improved health [32]. The difference may be in the follow-up period; the follow-up was 3 months in our study and one year in the comparative study.…”
Section: Discussioncontrasting
confidence: 83%
“… 36–38 A previous BELCODAC study reported that, in 2015, 21% of patients visited a physician for adults with CHD, 86% had a GP visit, 17% of patients had an ED visit, and 17% were hospitalized at least once. 38 On top of that, we know from studies in other chronic patient populations that healthcare utilization increases in the last months of life, mainly as a response to the presence of comorbidities and exacerbations at the end of life. 39 Referral to palliative care has shown to decrease the number of inpatient stays and ICU admissions at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, access to neuropsychological services for people with complex CHD in Australia is limited and costly [ 58 ], which compounds the high financial burden associated with having a complex cardiac condition [ 59 ]. Minimizing socioeconomic barriers that limit access to neuropsychological services for people with complex CHD is becoming a recognized health priority [ 60 ].…”
Section: Discussionmentioning
confidence: 99%